2000
DOI: 10.1152/ajpcell.2000.279.6.c1751
|View full text |Cite
|
Sign up to set email alerts
|

BKCa channel activation by membrane-associated cGMP kinase may contribute to uterine quiescence in pregnancy

Abstract: We investigated the influence of pregnancy on large-conductance calcium-activated potassium channel (BK(Ca)) activity (NP(o)) and on channel expression in membranes of isolated human myometrial smooth muscle cells. NP(o) in inside-out patches was higher in pregnant myometria (PM) compared with nonpregnant myometria (NPM), and the half-maximal activation potential was shifted by 39 mV to more negative potentials. This effect was not due to an enhanced BK(Ca) channel expression. In the presence of cAMP kinase (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(40 citation statements)
references
References 43 publications
1
39
0
Order By: Relevance
“…that regulation occurs through a membrane-delimited pathway. This conclusion is consistent with other electrophysiological studies of the BK channel, where channel regulation by kinases has also been demonstrated in excised patches (7,8,29,(37)(38)(39)(40)(41)(42)(43). Our biochemical assays (Figs.…”
Section: Discussionsupporting
confidence: 92%
“…that regulation occurs through a membrane-delimited pathway. This conclusion is consistent with other electrophysiological studies of the BK channel, where channel regulation by kinases has also been demonstrated in excised patches (7,8,29,(37)(38)(39)(40)(41)(42)(43). Our biochemical assays (Figs.…”
Section: Discussionsupporting
confidence: 92%
“…Enhanced activity of BKCa channels in pregnancy is often due to differential phosphorylation rather than an increase in BKCa expression levels. The membrane-bound PKG activates BKCa channels in human non-laboring myometrium thus contributing to myometrial quiescence during gestation [25]. Similarly, in rats, BKCa isoforms inhibited by PKA phosphorylation decreased throughout pregnancy whereas expression of isoforms activated by PKA peaked at mid-gestation [20].…”
Section: Bkca Channelsmentioning
confidence: 99%
“…Numerous functions have been attributed to BK channels, including modulation of smooth muscle tone of blood vessels and uterus (Zhou et al, 2000;, synaptic neurotransmitter release (Robitaille and Charlton, 1992) and epithelial transport (Kunzelmann and Mall, 2002). Most recently, attention has been drawn to the BK channel as a critical player in blood pressure regulation and in the neurotropic effect of ethanol (Davies et al, 2003).…”
Section: Introductionmentioning
confidence: 99%